Becoming heroines : unleashing our power for revolution and rebirth - McLaughlin, Elizabeth Cronise (Portfolio / Penguin, 2021)
"What if women forgot everything they'd been taught and radically redefined modern leadership? For those who have spent years playing by the rules only to suffer the cost, and who are now ready to transform their world and work, a soulful guide to knowing their power and using it for change at the deepest levels. Catastrophic events give us an opportunity to question everything. With systems of inequity revealed as never before and the need for revolutionary change in the air, female leaders are stepping forward to reinvent the broken systems they once accepted. Becoming Heroines guides them to ditch the old rules and create new ones, starting with healing internalized trauma, understanding principles of equity and inclusion, and refusing to be silenced any longer. Elizabeth Cronise McLaughlin runs wildly popular leadership and activist programs for women willing to undergo the deep inner transformation that leads to rebirth. Now she's leading brave readers on a journey to reclaim power, prompting them to: Observe and unpack the structures of oppression with which women engage in their daily lives Confront and analyze their own internalized biases Listen, advocate and overthrow systems and institutions that work to keep women and all marginalized people out of power Engage the process of building a future world that creates freedom for all This book is a must-read for any leader who's ready to live out her values more radically, rise from the ashes of trauma and defeat, and lead us all to a better world"--